Metode dan Corak Tafsir al-Manār Karya Muhammad Abduh dan Muhammad Rasyid Ridha dalam Pembaruan Tafsir Modern - Muh Haslam Hafid; Andi Abdul Hamzah; Abdul Rahman Sakka (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2026)
Tafsir al-Manār is widely recognized as one of the most influential works of modern Qur’anic exegesis, reflecting the reformist ideas of Muhammad Abduh and his disciple, Muhammad Rashid Rida. This study aims to analyze the interpretive method, characteristics, and intellectual contributions of Tafsir al-Manār to the development of modern Qur’anic interpretation. Employing a qualitative approach through library research, this study relies on Tafsīr al-Qur’ān al-Ḥakīm al-Masyhūr bi Tafsīr al-Manār as the primary source, complemented by relevant books and scholarly publications. The findings indicate that Tafsir al-Manār adopts the taḥlīlī (analytical) method by interpreting Qur’anic verses sequentially while emphasizing their practical guidance for contemporary Muslim society. The commentary integrates tafsīr bi al-ma’thūr and tafsīr bi al-ra’y, accompanied by a critical evaluation of Isrā’īliyyāt narratives. Its dominant interpretive orientation is adabī ijtimā’ī, which seeks to relate the Qur’anic message to social reform, education, morality, and the intellectual revival of the Muslim community. The analysis of the interpretations of Q.S. al-Baqarah [2]: 62 and Q.S. Āli ‘Imrān [3]: 104 demonstrates that Abduh and Rashid Rida emphasize faith, righteous deeds, and social responsibility as the essential foundations for individual and societal progress. This study concludes that Tafsir al-Manār represents not only a Qur’anic commentary but also a significant reformist project that bridges the normative teachings of the Qur’an with the socio-intellectual challenges of the modern era.